Antibacterial Activity of Salam (Syzygium polyanthum) Leaves 70% Ethanolic Extract on Staphylococcus aureus and Staphylococcus epidermidis - Ayu Nala El Muna Haerussana; Wulan Putri Dwiastuti; Cindi Arwan Sukowati (Journal of Tropical Pharmacy and Chemistry, 2021)
Indonesia has a high diversity of potential medicinal plants, which are the second-largest number of indigenous medicinal plants in the world. Syzygium polyanthum, known as Indonesian Bay Leaf or Salam, easily found, widely used in Indonesia as a spice in cooking and traditional medicine. Salam contains secondary metabolites such as flavonoids, alkaloids, tannins, essential oils, sesquiterpenes, triterpenes, phenols, steroids, and saponins. Staphylococcus aureus and Staphylococcus epidermidis are the main bacteria that cause commensal infection and the most common nosocomial infections. This study aims to know the antibacterial activity of the Salam ethanolic extract against Staphylococcus aureusand Staphylococcus epidermidis bacteria. Salam leaves were extracted by 70% ethanol in the maceration method. Antibacterial activity was conducted by the disk diffusion method. The extract exhibits moderate activity (10.51±0.3 mm) at 75% of concentration and low activity (3.69±0.4 mm) at 100% of concentration against Staphylococcus aureus and Staphylococcus epidermidis respectively. The test showed that salam leaves extract had antibacterial activity against Staphylococcus aureus and Staphylococcus epidermidis.